Recombinant expression and coexpression of oyster defensin and proline-rich peptide in Komagataella phaffii - KESMEN, ZÜLAL; Erdem Büyükkiraz, Mine (Biotechnology and Applied Biochemistry, 2022)
© 2021 International Union of Biochemistry and Molecular Biology, Inc.Proline-rich peptide (CgPrp) and defensin (CgDef), oyster (Crassostrea gigas)-originated antimicrobial peptides (AMPs), were produced by the recombinant technique in Komagataella phaffii GS115 cells. For this purpose, the nucleotide sequences encoding the CgPrp and CgDef peptides were synthesized by the recursive PCR technique, and ligated in pPICZaA expression vector. Additionally, the expression cassettes of pPICZαA-CgDef and pPICZαA-CgPrp were combined using in vitro multimer ligation strategy to construct the coexpression vector pPICZaA-CgPrp-CgDef. The expression and coexpression vectors transformed into K. phaffii GS115 cells by electroporation. At the end of the 0.5% methanol-induced expression stage for 96 h, the recombinant peptides were purified from the culture medium. The concentrations of purified peptides were changed between 1.05 and 1.21 mg/L. The recombinant peptides successfully inhibited the growth of tested Gram-positive bacterial strains belonging to Staphylococcus aureus, methicillin-resistant S. aureus (MRSA), Listeria monocytogenes, and Bacillus cereus. The minimum inhibitory concentrations (MIC) of recombinant CgPrp, CgDef, and CgPrp-CgDef peptides against tested bacteria were in the range of 12.50–25.00, 18.75–75.00, and 5.80–11.60 pg/μl, respectively. The results of the study proved that the recombinant CgPrp, CgDef, and CgPrp-CgDef peptides expressed in K. phaffii might have good potential for the inhibition of common Gram-positive pathogenic bacteria, including drug-resistant MRSA.